The Effect of Completeness of Learning Planning Administration on The Implementation of Assessment in Early Childhood Education - Dinar Nur Inten; Masnipal Marhun (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
Early childhood is an individual who has millions of potential in him. This potential can grow and develop optimally if the stimulus provided is in accordance with their needs and interests. Stimulus can be realized if the Early Childhood Education Institution (PAUD) has a complete administration of learning planning and implementation of good assessment. However, evidence in the field explains that there are still many PAUD teachers who do not understand planning so that the assessment has not been carried out properly and correctly and the stilus provided is not optimal. The purpose of the study was to look at the completeness of lesson planning and its impact on the implementation of assessment. The research approach used is qualitative with descriptive methods, namely describing field results in the form of data and narratives. The object of research is 20 pre-school institutions in Greater Bandung. The results prove that the completeness of planning affects the implementation of assessments conducted by teachers and the results of the assessment also have an impact on child development.